EFFECT OF DIETARY INTAKE CONTAINING VITAMINS A, C AND E ON TUBERCULOSIS PATIENTS - Yasmin, Ratri; Zuhri , Fuad Minan (Jurnal Biosains Pascasarjana, 2025)
Tuberculosis is a chronic infectious disease that is almost universally natural, caused by Mycobacterium tuberculosis. TB has a strong relationship with vitamins A, C, and E. This is due to the modulating action of these vitamins in the inflammatory process. Data was collected through literature review from electronic databases such as PubMed and SCOPUS. The keywords are "Ascorbic Acid", "Vitamin A", "Vitamin E", "tocopherol", "tocotrienol", and "Tuberculosis". Of the 167 selected articles, 4 were analyzed Intake of foods containing vitamins A, C and E can strengthen the immune system in killing Mycobacterium tuberculosis by modulating the maturation and migration of T cells, inducing hydroxyl radicals due to tuberculosis disease. Intake of foods containing vitamins A, C and E in people with tuberculosis can affect the risk of developing tuberculosis disease and can accelerate healing in people with tuberculosis. Deficiencies in vitamins A, C and E can worsen TB disease and can lead to drug resistance.